Determining fertilizer phosphorus requirement of upland rice - Sahrawat, K.L. (Informa UK Limited, 2000)
Assessing the fertilizer phosphorus requirement (FPR) of crops is an important component of research for efficient and rational use of fertilizers. Soil and plant tests are used to determine the FPR of crops. Two methods were evaluated for determining the FPR of upland rice grown on an Ultisol in the humid forest zone of Cote d'Ivoire. The first method used a simple model based on P uptake using the equation: FPR=(Up‐U0)/PRF, where Up is P uptake at a given yield, Uo is P uptake from unfertilized soil, and PRF is the P recovery fraction of applied P. The parameters, U0, Up, and FPR were determined in field experiments for the rice cultivars grown on an Ultisol under rainfed upland conditions. The second method was based on the P applied, P uptake, and grain yield relationships for upland rice. First, P uptake at a given rice yield was determined from the relationship between total P uptake and grain yield. The amount of fertilizer P applied for the given P uptake and grain yield was then, determined from the relationship between P applied and P uptake. There was a good agreement between the observed values of FPR and the predicted values of FPR determined by the two methods. The results suggest that the simple model based on P uptake can be utilized for determining the fertilizer P requirements of crops.